Severe Acute Respiratory Syndrome Coronavirus 2 ORF8 Protein Inhibits Type I Interferon Production by Targeting HSP90B1 Signaling - Chen, Jiayi; Lu, Zixin; Yang, Xiuwen; Zhou, Yezhen; Gao, Jing; Zhang, Shihao; Huang, Shan; Cai, Jintai; Yu, Jianhai; Zhao, Wei; Zhang, Bao (Frontiers in Cellular and Infection Microbiology, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a global pandemic that has currently infected over 430 million individuals worldwide. With the variant strains of SARS-CoV-2 emerging, a region of high mutation rates in ORF8 was identified during the early pandemic, which resulted in a mutation from leucine (L) to serine (S) at amino acid 84. A typical feature of ORF8 is the immune evasion by suppressing interferon response; however, the mechanisms by which the two variants of ORF8 antagonize the type I interferon (IFN-I) pathway have not yet been clearly investigated. Here, we reported that SARS-CoV-2 ORF8L and ORF8S with no difference inhibit the production of IFN-β, MDA5, RIG-I, ISG15, ISG56, IRF3, and other IFN-related genes induced by poly(I:C). In addition, both ORF8L and ORF8S proteins were found to suppress the nuclear translocation of IRF3. Mechanistically, the SARS-CoV-2 ORF8 protein interacts with HSP90B1, which was later investigated to induce the production of IFN-β and IRF3. Taken together, these results indicate that SARS-CoV-2 ORF8 antagonizes the RIG-I/MDA-5 signaling pathway by targeting HSP90B1, which subsequently exhibits an inhibitory effect on the production of IFN-I. These functions appeared not to be influenced by the genotypes of ORF8L and ORF8S. Our study provides an explanation for the antiviral immune suppression of SARS-CoV-2 and suggests implications for the pathogenic mechanism and treatment of COVID-19.